Finding time : breathing space for women who do too much - Coxe, Paula Peisner (Sourcebooks NapervilleUS, 2000)
Provides 36 techniques for helping busy women to manage time efficiently by habitually eliminating time bandits, and making the best use of each day. Deals with issues including: managing others' expectations; learning to say no to others and yes to yourself; managing the telephone; establishing priorities; scheduling personal time; and delegating tasks.